Factors associated with musculoskeletal symptoms in professionals working in sitting position - Anália Rosário Lopes; Celita Salmaso Trelha; Maria Lúcia do Carmo Cruz Robazzi; Roberta Alvarenga Reis; Maria José Bistafa Pereira; Claudia Benedita dos Santos (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To estimate the prevalence of musculoskeletal symptoms and analyze their associated factors in professionals from administrative sectors working predominantly in sitting position. METHODS This is a cross-sectional study with data obtained from 451 workers from a federal public institution in Southern Brazil. The dependent variable was the number of musculoskeletal symptoms in the prior 12 months, measured using the Nordic Musculoskeletal Questionnaire. In the analyses, 19 independent variables were investigated, divided into four categories: sociodemographic, behavioral, occupational and health characteristics. Univariate analysis and multiple Poisson regression with robust variance were performed. The independent variables were inserted into blocks with stepwise backward criterion, considering the value for Wald statistics equal to 0.20. The effect measures were expressed in a relative increase (RI) in the mean value, and the data were analyzed for a 5% significance level. RESULTS The estimated prevalence of musculoskeletal symptoms in the prior 12 months was 90% (confidence interval - 95%CI 87-93). In the final model of regression analysis, the variables female gender (RI = 14.75%), low (RI = 100.02%) and moderate (RI = 64.06%) work ability index, use of medications (RI = 48.06%) and waist circumference at risk (RI = 15.59%) had a significant association with the increase in the mean number of symptoms; schooling with technical education acted as a protective factor, reducing the mean by 36.46%. CONCLUSIONS The high prevalence of musculoskeletal symptoms found and the associated factors indicate the need to propose specific actions and care for this population, such as immediate treatment of symptoms and changes in the organization and work environment, to achieve balance and harmony in the demands of prolonged sitting work and avoid its impact effect of this condition on public health.